2022
DOI: 10.3389/fpsyg.2022.831060
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transformational Leadership on Affective Organizational Commitment and Job Performance: The Mediating Role of Employee Engagement

Abstract: This study investigated the impact of transformational leadership on affective organizational commitment and job performance with the mediating role of employee engagement. This study gathered data from 845 hotel employees in China and the structural equation modeling technique was used to verify the results. The findings indicated that transformational leadership has a positive effect on affective organizational commitment and job performance. Meanwhile, results showed that employee engagement partially media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 118 publications
8
35
0
2
Order By: Relevance
“…To measure transformational leadership, we adapted eight items from the prior study by 56 . Existing researchers widely used this scale 39,66 . A sample item is ‘I believe the leader can overcome any challenge at work.’ The Cronbach's alpha for transformational leadership was 0.938.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure transformational leadership, we adapted eight items from the prior study by 56 . Existing researchers widely used this scale 39,66 . A sample item is ‘I believe the leader can overcome any challenge at work.’ The Cronbach's alpha for transformational leadership was 0.938.…”
Section: Methodsmentioning
confidence: 99%
“…56 Existing researchers widely used this scale. 39,66 A sample item is 'I believe the leader can overcome any challenge at work.' The Cronbach's alpha for transformational leadership was 0.938.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…In return, they receive timely appreciation and encouragement, thereby making organizations grow (Holt, 2018). As such, previous studies on the transformative leadership style consistently showed that the transformative leadership style has a positive relationship with innovative work behavior and delivery of results (Jiatong et al, 2022;Yang et al, 2020;Lai et al, 2020;Eliyana et al, 2019). The following questions will be explored in this study.…”
Section: Previous Research and Hypothesesmentioning
confidence: 99%
“…Different leadership styles have been related to employee commitment, this includes between others transformational leadership ( Avolio et al, 2004 ; Keskes et al, 2018 ; Jiatong et al, 2022 ), servant leadership ( Lapointe and Vandenberghe, 2018 ), spiritual leadership ( Sapta et al, 2021 ), and authentic leadership ( Ausar et al, 2016 ). This can be explained because several leadership behaviors like decentralization in decision-making, perceived organizational support, perception of importance for the organization ( Meyer and Allen, 1991 ), and perceived organizational support ( Rhoades et al, 2001 ; Meyer et al, 2002 ) have been identified as determinants of AOC.…”
Section: Literature Analysis and Hypothesis Developmentmentioning
confidence: 99%